The Effect of Seeding Rate on Growth and Yield of "Sidi Misri F Wheat (Triticum aestivum L.) - SOROUR, F. A.; EL-SHARKAWY, M. A. (The Libyan Journal of Agriculture, 2023)
he effect of seeding rate on the growth and yield of‘Sidi Misri 1 ’ wheat was studied in two seasons; 1973 and 1974. at the Faculty of Agriculture Farm. Tripoli. Plant height and spike length were decreased by increasing the seeding rate in both growing seasons. In the 1973 experiment, the maximum grain yield of 2.062 ton/ ha was obtained with a seeding rate of 100 kg/ha, and the lowest yield, 1.587 ton/ha with a seeding rate of 60 kg/ha. In the second experiment of 1974, however, the maximum grain yield, 1.796 ton/ha resulted when the seeding rate was 75kg/ha and the lowest 1.328 ton/ha resulted with 30 kg/ha. On plant basis, the average grain yield, number of grains, and number of tillers per plant decreased with increasing the seeding rate. On the other hand, straw yield, grain to straw ratio, and grain size were not significantly affected by seeding rate. It was concluded that the optimum rate of seeding ranged from 75 to 100 kg/ha.